Cardiac Myxoid Spindle Cell Tumor in a Neonate - Reza Abbaszadeh; Fatemeh Naderi; Amir Hossein Jalali; Yaser Toloueitabar (Hindawi Limited, 2024)
Introduction: Different subtypes of cardiac tumors containing spindle cells have been described as cardiac sarcoma. However, benign types have not been reported so far. We described a neonate with progressive respiratory distress who had a PDA and was finally diagnosed with a right atrial spindle cell tumor. Case Presentation: The patient was a neonate referred with respiratory distress and sepsis. The initial echocardiography demonstrated a small atrial septal defect, patent ductus arteriosus, and a heterogeneous rounded right atrial mass lesion. Pathologic examination confirmed the right atrial myxoid spindle cell tumor without local invasion. Successful mass resection was performed, and follow-up echocardiography revealed normal cardiac structure and function. Conclusion: In infants with manifestations of possible cardiac anomalies, it is necessary to consider other pathologies, such as neoplastic processes. Spindle cell detection in pathology is not ominous all the time, and there are benign subtypes with favorable outcomes after successful surgical resection.